Food insecurity and its severity among adults receiving antiretroviral therapy in health facilities, northcentral Ethiopia: a multi-facility-based cross-sectional study - Boneya, Dube Jara; Ahmed, Ahmed Ali; Yalew, Alemayehu Worku (Frontiers in Public Health, 2024)
Background Food insecurity plays a crucial role in predicting the spread of HIV due to the adverse effects of coping mechanisms adopted to mitigate it. However, there is a scarcity of context-specific evidence regarding food insecurity among HIV-infected adults. Therefore, this study aimed to assess the context-specific magnitude of food insecurity and associated factors among adults receiving antiretroviral therapy (ART) in health facilities in the North Shewa Zone, Ethiopia, ultimately contributing to the achievement of the 95–95-95 HIV treatment target in the local context. Methods A multi-facility cross-sectional study was conducted among 865 HIV-infected adults receiving ART and being followed up for their treatment. We included health facilities that provide ART, including four hospitals and six health centers. A log-binomial regression model was fitted to identify the association between food insecurity and independent variables. Adjusted prevalence ratios (APRs) with a 95% confidence interval were computed to measure the strength of the association. Results In this study, 290 (33.7, 95% CI: 30.60, 36.91) of the HIV-infected adults studied had food insecurity during their treatment and follow-up, of which 152 (52.41, 95% CI: 46.64, 58.13) and 110 (37.93%, CI: 32.50, 43.68) of them were found to have severe and moderate forms of food insecurity, respectively. We found that being younger (APR = 2.27, 95% CI: 1.12, 4.60), being female (APR = 1.87, 95% CI: 1.03, 3.39), lacking formal education (APR = 10.79, 95% CI: 14.74, 24.58), having lower educational status (APR = 5.99, 95% CI: 2.65, 13.54), being a daily laborer (APR = 6.90, 95% CI: 2.28, 20.85), having low monthly income (APR = 1.89, 95% CI: 1.11, 3.22), advanced WHO clinical stage (APR = 2.34, 95% CI: 1.08, 5.10), and receiving ART for less than 4 years (AOR = 2.28, 95% CI: 1.09, 4.74) were significantly associated with a high proportion of food insecurity among HIV-infected adults. Conclusion The magnitude of food insecurity among HIV-infected adults receiving ART was high, with an extremely high magnitude of severe food insecurity. The finding suggests the need for culture- and context-specific nutritional interventions to address the gender dynamics of food insecurity, attention to the early stage of ART, and the integration of strategies to improve educational status and enhance income-generation activities of HIV-infected adults. This requires an emphasis on the link between food insecurity and HIV in Ethiopia’s national food and nutrition policy.